Conservation Subdivision: Construction Phase – Protecting Trees and Conserved Natural Areas - Mark Hostetler; Glenn Acomb (EDIS)
WEC278, a 6-page illustrated fact sheet by Mark Hostetler and Glenn Acomb, discusses techniques and strategies that minimize impacts of the construction process on conserved trees and natural areas. Includes additional resources. Published by the UF Department of Wildlife Conservation and Ecology, March 2010.